The Relationship of HbA1c Levels with Symptoms of Gastroesophageal Reflux Disease (GERD) in Type 2 Diabetes Mellitus Patients at Prof. Dr. Soekandar Mojokerto Hospital - Aisha Shafwina Althaf; Hendrata Erry Andisari; Fitri Handajani (Journal of Social Research, 2026)
This study aims to investigate the relationship between HbA1c levels and the occurrence of gastroesophageal reflux disease (GERD) symptoms in patients with Type 2 diabetes mellitus (T2DM) at Prof. Dr. Soekandar Hospital, Mojokerto. The prevalence of GERD in diabetic patients, particularly those with poor glycemic control, is a growing concern globally. The primary objective was to determine whether varying HbA1c levels correlate with the severity of GERD symptoms, as measured using the GERD-Q score. A cross-sectional observational design was employed, with data collected through HbA1c measurements and GERD-Q questionnaires from 52 patients with T2DM. The study utilized both univariate and bivariate analyses, including chi-square tests, to evaluate the relationship between glycemic control and GERD symptoms. The results indicated a significant association between higher HbA1c levels and increased GERD prevalence, with 88.9% of patients in the uncontrolled HbA1c group exhibiting GERD symptoms. The chi-square test revealed a significant p-value of <0.001, confirming a strong correlation between poor glycemic control and GERD incidence. This study highlights the importance of glycemic control in reducing the risk of gastrointestinal complications, particularly GERD, in patients with T2DM. Further research is needed to explore the pathophysiological mechanisms underlying this relationship and to develop targeted clinical interventions.